A reappraisal of the family status of Neotropical Protoneuridae (Odonata: Zygoptera) using morphological and molecular information - Pessacq, Pablo (2025)
Several comprehensive studies have greatly contributed to the clarification of Odonata phylogeny, paying special attention to the damselflies (Zygoptera). Nearly half of the species of Zygoptera are included in the family Coenagrionidae, but the status of some previously recognized families is still debated. Here, we present the results of phylogenetic analyses based on nuclear and mitochondrial sequences and morphological data of 10 of the 15 Neotropical genera formerly included within the Neotropical family Protoneuridae, with the goal to test their monophyly and phylogenetic position within the Coenagrionidae sensu lato. Our analyses support the polyphyly of Protoneuridae, with Proneura prolongata and Junix elumbis falling within the “core” Coenagrionidae, whereas the remaining Neotropical Protoneuridae included in our analyses form a monophyletic clade, sister to the ridged frons Coenagrionidae. Our results differ from previous analyses that suggested that the Protoneuridae were members of the ridged frons Coenagrionidae clade, most likely because our dataset has a wider coverage of the group, both in terms of taxa and data sources. We propose the redefinition of the Protoneuridae (excluding Proneura,Junix and all the previously included Old World genera) and its re-establishment as a redefined Protoneuridae family, which is characterized by several morphological and biological unique attributes.